Traditional Biotechnology Approaches in Halal Food Production: A Comprehensive Review - Ashari Harunaningtyas; Nanda Legiasa Rabiul Tsani Rohana (Universitas Darussalam Gontor, 2025)
The concepts of halaland thayyib arekey considerations in Muslim-majority nations. Halaland thayyib are the highest quality standards, as well as indicators of product competitiveness. This concept can be applied to all productsor services consumed. Traditional biotechnology is one applicationofthehalal and thayyib principle.Traditional biotechnology involves the activity of microorganisms, namely, fermentation. Fermented products include tape, kombucha, yogurt, bread, and tauco. These five products are well known within Muslim communities,hence the need for critical examination of their halal and thayyib aspects. In terms of halal, fermented products must ensure the halalstatus of the raw materials, media used, and food additives. Meanwhile, in terms of thayyib, fermented products must ensure food safety, process hygiene, and the use of high-quality raw materials, thereby allowingMuslim consumerstofeel safe andconfident in consuming these products.